Comparative literature for the new century - De Gasperi, Giulia; Pivato, Joseph (McGill-Queen's University Press, 2018)
Since its beginning, Comparative Literature has been characterized as a discipline in crisis. But its shifting boundaries are its strength, allowing for collaboration and growth and illuminating a path forward. In Comparative Literature for the New Century a diverse group of scholars argue for a distinct North American approach to literary studies that includes the promotion of different languages. Chapters by senior scholars such as George Elliott Clarke, E.D. Blodgett, and Sneja Gunew are placed in dialogue with those by younger scholars, including Dominique Hétu, Maria Cristina Seccia, and Ndeye Fatou Ba. The writers, many of whom are multilingual, discuss problems with translation, identity and belonging, the modern epic, the role of tradition, minority writing, Francophone and Anglophone novels in Africa, and politics in literature. Engaging with theory, history, media studies, psychology, translation studies, post-colonial studies, and gender studies, chapters exemplify how the knowledge and tools offered by Comparative Literature can be applied in reading, exploring, and understanding not only literary productions but also the world at large. Presenting some of the most current work being carried out by academics and scholars actively engaged in the field in Canada and abroad, Comparative Literature for the New Century promotes the value of Comparative Literature as an interdisciplinary study and assesses future directions it might take. Contributors include George Elliott Clarke (University of Toronto), Dominique Hétu (Alberta & Montreal), Monique Tschofen (Ryerson), Jolene Armstrong (Athabasca), E.D. Blodgett (Alberta), Ndeye Fatou Ba (Ryerson), Maria Cristina Seccia (Hull), Sneja Gunew (UBC), Deborah Saidero (Udine), Elizabeth Dahab (CSULB), Gaetano Rando (Wollongong), Anna Pia De Luca (Udine), Mark A. McCutcheon (Athabasca), Giulia De Gasperi (PEI), and Joseph Pivato (Athabasca).